Extension of the method of quasilinearization for stochastic initial value problems. (1995) - Shahzad, N.; McRae, Farzana A.
Abstract : In this paper we extend the method of quasilinearization to stochastic initial value problems. Further we prove that the iterates converge uniformly almost surely to the unique solution and the convergence is quadratic.